A novel class of ZNF384 aberrations in acute leukemia - Zaliova, Marketa; Winkowska, Lucie; Stuchly, Jan; Fiser, Karel; Triska, Petr; Zwyrtkova, Martina; Hrusak, Ondrej; Starkova, Julia; Sramkova, Lucie; Stary, Jan; Trka, Jan; Zuna, Jan (Blood advances, 2021)
Fusion of the ZNF384 gene as the 3' partner to several different 5' partner genes occurs recurrently in B-cell precursor acute lymphoblastic and mixed phenotype B/myeloid leukemia. These canonical fusions (ZNF384r) contain the complete ZNF384 coding sequence and are associated with a specific gene expression signature. Cases with this signature, but without canonical ZNF384 fusions (ZNF384r-like cases), have been described previously. Although some have been shown to harbor ZNF362 fusions, the primary aberrations remain unknown in a major proportion. We studied 3 patients with the ZNF384r signature and unknown primary genetic background and identified a previously unknown class of genetic aberration affecting the last exon of ZNF384 and resulting in disruption of the C-terminal portion of the ZNF384 protein. Importantly, in 2 cases, the ZNF384 aberration, indel, was missed during the bioinformatic analysis but revealed by the manual, targeted reanalysis. Two cases with the novel aberrations had a mixed (B/myeloid) immunophenotype commonly associated with canonical ZNF384 fusions. In conclusion, we present leukemia cases with a novel class of ZNF384 aberrations that phenocopy leukemia with ZNF384r. Therefore, we show that part of the so-called ZNF384r-like cases represent the same genetic subtype as leukemia with canonical ZNF384 fusions.
Keywords: transkriptom; Trans-Activators; Immunophenotyping; trans-aktivátory; Transcriptome; akutní myeloidní leukemie; lidé; Transcription Factors; transkripční faktory; Humans; Leukemia, Myeloid, Acute; imunofenotypizace